The Effect of Thermal Treatment on the Resistance of 7075 Aluminum Alloy in Aggressive Alkaline Solution - Araoyinbo, Alaba Oladeji; Abdullah, Mohd Mustafa Al Bakri; Rahmat, Azmi; Azmi, Azwan Iskandar; Wan Abd Rahim, Wan Mohd Faizal; Jamil, Noorina Hidayu; Jin, Tan Soo (Journal of Science and Technology, 2018)
Aluminum has attractive properties in which when properly engineered can be used in wider areas of applications. Due to its reactive abilities and strong affinity for oxygen, aluminum can resist rough environments and overall durable to various chemical agents. This work highlighted the behaviour of 7075 aluminum alloy in an aggressive alkaline environment. Two tempers of T6 and T73 were produced through solution heat treatment procedure; the T6 temper was subjected to solution heat treatment at 470°C for 60 min, quenched for 60 sec and followed by precipitation heat treatment or artificial ageing at 138°C for 960 min whereas the T73 was subjected to solution heat treatment at 470°C for 60 min quenched for 60 sec and followed by two precipitation heat treatment processes at 113°C for 480 min and 182°C for 720 min respectively.  The as received and the tempered materials are immersed in an aggressive alkaline medium consisting sodium chloride and hydrogen peroxide. The samples obtained were characterized by assessing weight loss and subjected to surface morphology analysis using scanning electron microscope. The morphology of the heat treated samples shows the type of localized form of corrosion present is pitting form of corrosion, and the weight analysis shows significant weight loss when the samples are exposed to the aggressive alkaline environment. The weight loss for the as received sample was observed to be more than the T73 and the T6 samples.